Controlling Porosity in Lignin‐Derived Nanoporous Carbon for Supercapacitor Applications. Issue 3 (22nd January 2015) - Jeon, Ju‐Won; Zhang, Libing; Lutkenhaus, Jodie L.; Laskar, Dhrubojyoti D.; Lemmon, John P.; Choi, Daiwon; Nandasiri, Manjula I.; Hashmi, Ali; Xu, Jie; Motkuri, Radha K.; Fernandez, Carlos A.; Liu, Jian; et al.
Abstract Invited for this month′s cover is a group of collaborators led by Satish Nune at Pacific Northwest National Laboratory. The image shows the path to renewable energy storage using high surface area carbons derived from low‐cost renewable lignin. The Communication itself is available at 10.1002/cssc.201402621.